2017
DOI: 10.1007/s40864-017-0052-6
|View full text |Cite
|
Sign up to set email alerts
|

Public Perception of and Attitude to Driverless Train: A Case Study of Sydney, Australia

Abstract: There are 32 cities around the world with automated metro systems in operation. The majority of these are located in Europe (13) and Asia (14) but none so far in Australia. However, the picture is changing in 2019 when the first stage of the 'Sydney Metro' starts its operation on the North West link in Sydney, New South Wales, Australia. The automated train is planned to be used safely without human interaction, thus reducing significantly the labour input in the provision of service. Although the proposal for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 15 publications
2
20
1
Order By: Relevance
“…In this regard, research on automated vehicle acceptance would profit from drawing analogies to other domains, such as driverless trains and even pilotless aircraft. Fraszczyk and Mulley (2017) found that respondents rated having a driver on driverless trains as (very) important and preferred to include a driver cab on driverless trains. Rice et al (2014), who investigated opinions about autonomous auto-pilots for commercial flights, found that respondents were more comfortable/trusting/willing to use the aircraft with the human pilot in comparison to the auto-pilot (fully autonomous machines that operate without interference with human pilots), or a human pilot in a ground station remotely controlling the aircraft.…”
Section: Trustmentioning
confidence: 99%
“…In this regard, research on automated vehicle acceptance would profit from drawing analogies to other domains, such as driverless trains and even pilotless aircraft. Fraszczyk and Mulley (2017) found that respondents rated having a driver on driverless trains as (very) important and preferred to include a driver cab on driverless trains. Rice et al (2014), who investigated opinions about autonomous auto-pilots for commercial flights, found that respondents were more comfortable/trusting/willing to use the aircraft with the human pilot in comparison to the auto-pilot (fully autonomous machines that operate without interference with human pilots), or a human pilot in a ground station remotely controlling the aircraft.…”
Section: Trustmentioning
confidence: 99%
“…Second, another potential topic for future studies could be a comparative perspective on the acceptance of different automated passenger services. For example, Fraszczyk and Mulley [29] analyzed public perceptions of driverless train operations (with attendants) and unattended train operation. Third, testing critical AV issues in a choice setting might yield real-world results that could identify the contributions of specific factors relative to classic attributes, such as time and costs.…”
Section: Discussionmentioning
confidence: 99%
“…Few examples of pre-launch studies were found to look at new or proposed railways. For instance, Fraszczyk and Mulley [25] carried out research on public perception of an automated metro system in Sydney, Australia. They investigated what Sydney-siders think about the new driverless train.…”
Section: Pre-launch Perception Of Public Transport Servicesmentioning
confidence: 99%